Comparative Analysis and Trends in Indonesian Population as National Resource Potential According to a War History Perspective - Muslikhatin, Lilik; Renta , Hotma; Morolawe, Morolawe (PT FORMOSA CENDEKIA GLOBAL, 2024)
History teaches that every time a war occurs, one important factor that cannot be ignored is troop mobilization. In the wars that have occurred so far, whether World War I, World War II, or other wars, the majority of victories were determined by the number of troops the winning party had. Management of national resources, one of which is the population as troops, requires good handling and preparation in facing the threat of war. Both conventional wars which are currently occurring in other parts of the world, such as Israel-Palestine or Russia-Ukraine, as well as asymmetric wars which also threaten the security and safety of the nation. This article discusses the human resources that the Indonesian state has to prepare reliable personnel to face the threat of war. The analysis used is a comparative gender analysis between men and women and an analysis of trends in the population of productive age projected until 2030. So far, troops or human resources have often been interpreted as only men being able to face threats. Female human resources are also widely available and can work alongside men if they are trained and managed well.